Have credit card services become important to monetary aggregation? An application of sign restricted Bayesian VAR - William A. Barnett; Hyun Park (Journal of Applied Economics, 2024)
The purpose of this paper is to estimate the relationship among a primary set of economic variables, including two types of monetary aggregates: simple sum M2 and credit-card-augmented Divisia inside money services. The importance of that comparison has grown as the use of credit cards in purchase transactions has expanded. The data period includes the Great Recession, which was heavily associated with finance and thereby especially relevant to this study. The basic methodology in this paper is VAR-Sign Restrictions estimation. VAR is a well-known method to analyze inter-dependency among economic variables. By applying VAR-Sign Restrictions, we analyze how economic variables behave, positively or negatively, toward differently defined shocks. Imposing signs on the direction of economic variable responses to shocks is based on economic prior beliefs, using Bayesian estimation. Our results provide deeper insights into the relative merits of the two types of monetary aggregates as indicators.
Keywords: 330; Aggregation theory; Bayesian estimation; Credit-card-augmented divisia monetary aggregate; VAR-Sign Restriction